Análise da viabilidade de implantação de um sistema de aproveitamento de águas pluviais para a Escola Manoel Carlos Silva de Tucuruí-PA - TEIXEIRA, Mísley da Cruz (2022)
Brazil is a country that, despite having an abundance of water resources, suffers from water scarcity problems in some of its regions due to uneven distribution of the same. The worsening of water scarcity in some regions is mainly related to changes in the hydrological cycle, usually resulting from environmental degradation, population growth, industrialization, irrational use of water and pollution of water sources. This situation stimulated the search for alternative sources of supply and water conservation techniques, such as the rainwater utilization. With the aim of spreading this technique in the town, this work shall, by means of water balance and the Net Present Value (NPV), the technical and economic feasibility of implementing a rainwater utilization system proposed for a public building. To do so, it was done: the statistical analysis of rainfall data in the region; sizing and adaptation of storm drainage and cold water’s networks of the building, specifically the reservoir by interactive method; the estimation of non-potable consumption of the building; the analysis of the technical feasibility through the monthly water balance of the system and the quantification of supply demand for rainwater ; the elaboration of project budget, through the composition of unit costs; and the application of NPV to analyze the financial viability. The results showed the town’s precipitation regime (rainy season from December to May and dry from June to November), proved the technique of the enterprise unviable, with attendance least 30% of non-potable demand of the building, and pointed out the payback period investment, 8 years, with NPV of R$ 38 058,09 at the end of 30 years, it was the useful life of the project.